Determinants of Capital Structure and Interacted Impact with Environmental dynamism on Firms Performance: Evidence from Chinese Listed Companies - Tang, Yuan (2012)
This paper employs a new database of 212 Chinese listed companies from Hushen 300 index during the period of 2007-2011. The study finds that leverage of Chinese listed firms increases with fixed asset and proportion of non-tradable shares, and decreases with profitability and growth opportunities. It does not find significant effect of capital structure by firm size, non-debt tax shields and tax rate. Volatility of earnings is significantly negatively related with long-term leverage. Environment dynamism and leverage have significantly negative impact on firms’ performance while size is positively rated with firms’ performance. Evidence shows no significant relation between firms’ performance and the interaction of dynamism and capital structure.